Leiomyosarcoma of the Right Gonadal Vein: Review of the Approach and Prognostic in a Rare Case - Noa de la Fuente; Manuel Rodríguez Blanco; Gemma Cerdán; Antonio Moral; Vicenç Artigas (Case Reports in Surgery)
Background. Venous leiomyosarcoma is a mesenchymal tumour that represents 5-7% of soft tissue sarcomas. It originates in the smooth muscle cells of the vessel wall and is frequently located in the inferior vena cava. Primary leiomyosarcomas of the gonadal vein are rare, with only 10 cases reported in the literature. Case report. We present the case of a 51-year-old woman diagnosed with a right retroperitoneal mass by computed tomography (CT). The differential diagnosis was between a neurogenic tumour and a mesodermic tumour. The tumour was dissected from the vena cava and right ureter by laparoscopy without performing resection en bloc. Histologic examination of the surgical specimen showed a high-grade leiomyosarcoma of the right gonadal vein. The postoperative course was uneventful. Three cycles of chemotherapy with epirubicin-ifosfamide were performed. Discussion and conclusions. Venous leiomyosarcoma is an aggressive tumour, and prognosis is poor due to haematogenous spread. No chemotherapy or radiotherapy has yet proven effective in improving survival, and complete surgical excision is currently considered to offer the best chance of cure. Despite the more conservative treatment approach used in the present case, the patient is alive three years after surgery and has a good quality of life. Although it was not used in this patient, the standard procedure for optimal survival is resection en bloc.